2006
DOI: 10.1262/jrd.17088
|View full text |Cite
|
Sign up to set email alerts
|

A New Perspective on Management of Reproduction in Dairy Cows: the Need for Detailed Metabolic Information, an Improved Selection Index and Extended Lactation

Abstract: Abstract.For lactating dairy cows, we need management tools, that are "clean, green and ethical", cost-effective and easy to use. Specific tools are needed for artificial insemination (AI) after oestrus detection within a few months of calving, and for managing the complex nutritional requirements of cows between successive calvings. Assessment of energy deficit by measurement of body condition score (BCS) has been useful in the past but we now need more sophisticated ways to measure the relationship between a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 33 publications
0
23
1
Order By: Relevance
“…2008). These relationships between MY and health vary among herds and between cows within a herd (Kadokawa 2006). We found no significant differences between the MY groups regarding culling due to the movement disorders, mammary gland diseases, and a low fertility.…”
Section: High-producing Dairy Herdmentioning
confidence: 55%
“…2008). These relationships between MY and health vary among herds and between cows within a herd (Kadokawa 2006). We found no significant differences between the MY groups regarding culling due to the movement disorders, mammary gland diseases, and a low fertility.…”
Section: High-producing Dairy Herdmentioning
confidence: 55%
“…In our study, the highest net profit (−0.63 ± 0.42 CZK per L of milk), the highest profitability of costs (−6.45 ± 4.44%), and lowest total costs (8.41 ± 0.40 CZK per L of milk) occurred in the group of herds with CI ≤ 389 d (P < 0.05). However, some studies do not agree with this and consider that the problem lies in the inadequate management of high-producing herds, the level of the lactation persistency, and the genetic potential of animals (Pryce et al 2001;Kadokawa and Martin 2006). Arbel et al (2001) investigated the effect that extending the lactation has on the milk production and profitability in the following lactation.…”
Section: Optimal Calving Interval and Profitmentioning
confidence: 99%
“…According to Koc (2012), it is possible to achieve a significantly higher milk production from cows with CI of more than 400 d but less than 500 d. Pryce et al (2001) found the genetic correlation between the milk production and CI to be between r = 0.22 and r = 0.59. Kadokawa and Martin (2006) added that extending CI could help cows with extremely high yields. Therefore, higher milk yields and shorter CI is not always the most profitable combination.…”
Section: Optimal Calving Interval and Profitmentioning
confidence: 99%
“…, nutrition (Kadokawa and Martin, 2006;Robinson et al, 2006;Chagas et al, 2007;Friggens and Newbold, 2007;Wathes et al, 2007) Economics (Vargas et al, 2002;Esslemont, 2003;Santarossa et al, 2004;McGuirk et al, 2007), veterinary interventions and management (Refsdal, 2000;Roche et al, 2000;Sheldon et al, 2004;Bertoni et al, 2006;Diskin et al, 2006;Drillich et al, 2006;Mansell et al, 2006;Mee, 2007;Valergakis et al, 2007). It has also prompted the development of new technology and applications in the field.…”
mentioning
confidence: 99%